Effect of Usnic Acid on Candida orthopsilosis and C. parapsilosis - Pires, Regina Helena [UNESP]; Lucarini, Rodrigo; Mendes-Giannini, Maria José Soares [UNESP] (Amer Soc Microbiology, 2012)
The activity of usnic acid against Candida orthopsilosis and Candida parapsilosis on planktonic and biofilm conditions was investigated by using a broth microdilution and microplate methods. Potent in vitro activities against different Candida species were obtained. The metabolic activity of sessile cells of C. parapsilosis complex was reduced by 80% at four times the 80% inhibitory concentration. The in vitro studies support further efforts to determine whether usnic acid can be used clinically to cure patients with Candida infections.